An ionic electro-active actuator made with graphene film electrode, chitosan and ionic liquid. (13th May 2015) - He, Qingsong; Yu, Min; Yang, Xu; Kim, Kwang Jin; Dai, Zhendong
Abstract: A newly developed ionic electro-active actuator composed of an ionic electrolyte layer sandwiched between two graphene film layers was investigated. Scanning electronic microscopy observation and x-ray diffraction analysis showed that the graphene sheets in the film stacked in a nearly face-to-face fashion but did not restack back to graphite, and the resulting graphene film with low sheet resistance (10 Ω sq −1 ) adheres well to the electrolyte membrane. Contact angle measurement showed the surface energy (37.98 mJ m −2 ) of the ionic electrolyte polymer is 2.67 times higher than that (14.2 mJ m −2 ) of the Nafion membrane, contributing to the good adhesion between the graphene film electrode and the electrolyte membrane. An electric double-layer is formed at the interface between the graphene film electrode and the ionic electrolyte membrane under the input potential, resulting in a higher capacitance of 27.6 mF cm −2 . We report that this ionic actuator exhibits adequate bending strain, ranging from 0.032 to 0.1% (305 to 945 μ m) as functions of voltage.